THE CORRELATION BETWEEN GRAMMAR AND SPEAKING SKILL OF UNDERGRADUATE STUDENTS - Fakhruddin Zam Zam; Aminah Suriaman; Rofiqoh Rofiqoh; Budi Budi (Universitas Muhammadiyah Makassar, 2021)
This research aims to find out correlation between grammar and speaking skill of the third semester students of English Education Study Program academic year 2019/2020 at IAIN Datokarama Palu. 28 participants of correlational research were asked to describe themselves, daily routines, and unforgettable experience. Then, they were assigned to do grammar test. The data were analyzed using Pearson Product Moment Correlation Coefficient. The result shows that the correlation coefficient between students’ grammar and speaking skill is 0.46. The result is categorized “moderate” (0.40 to 0.59). It indicates that there is positive correlation between the students’ grammar and speaking skill which means that grammar contributes to speaking skilll, but grammar is not the main predictor of speaking skill achievement. There are some other aspects of speaking affecting the students’ speaking skill, i.e accuracy (in terms of vocabulary and pronunciation), fluency, and comprehensibility. The implication of this finding to the teaching of speaking skill is that the lecturers need to integrate the teaching of speaking skill with grammar and other supporting aspects, like vocabulary and pronunciation.